Chapter 6 The road to Anti-Trafficking Inc. Transformative tipping points for socially sustainable global value chains - Narminio, Elisa (Taylor & Francis, 2023)
This Chapter examines the regulatory and voluntary anti-trafficking governance architecture in the private sector, as well as the power dynamics in MNEs' GVCs as vectors of norm transmission. It argues that, whereas the public authorities in the EU and ASEAN's Member States have an increasingly robust legal and policy framework to fight child trafficking, public authorities and multinational enterprises (MNEs) are jointly contributing to upholding the exploitative practices towards children, by leaving untouched the economic structures that fuel trafficking. The model is starting to be overhauled in some sectors of the economy, through strategies to gain back control over GVCs, whether through the shortening of supply chains, or other strategies such as the establishment of direct relations with small producers, who are given a fairer deal compared to situations when they are end producers in long GVCs. It will require more efforts to scale up these initiatives and create sufficient momentum to efficiently combat anti-trafficking, otherwise "blue" initiatives of social sustainability risk leading to further sustainability-driven supplier-squeezes, reinforcing the divide between small businesses and large corporations, and increasing the structural vulnerability of children to trafficking.